Capturing Local Material Heterogeneities in Numerical Modelling of Microstructure Evolution - Madej, Lukasz; Sitko, Mateusz; Fular, Aleksander; Sarzyński, Rafał; Wermiński, Mariusz; Perzyński, Konrad (Journal of machine engineering, 2021)
The work focuses on developing the complex digital shadow of the metallic material microstructure that can predict its evolution during metal forming operations. Therefore, such a digital shadow has to consider all major physical mechanisms influencing the particular investigated phenomenon. The motivation for the work is directly related to the development of modern metallic materials, often of multiphase nature, which leads to local heterogeneities influencing microstructure behavior and eventually macroscopic properties of the final product. The concept of the digital microstructure shadow, stages of the model development, and examples of practical applications to simulation of microstructure evolution are presented within the work. Capturing local heterogeneities that have a physical origin and eliminating numerical artifacts is particularly addressed. Obtained results demonstrate the capabilities of such a digital microstructure shadow approach in the numerical design of final product properties.